Two‐Year Changes in Remnant Cholesterol and Stroke Risk in the Chinese Population: A Prospective Cohort Study - Dan Wang; Zifei Zhang; Yijun Zhang; Shuohua Chen; Nan Qu; Haibin Li; Yongkang Sun; Xue Tian; Xinsheng Han; Shouling Wu; Anxin Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Previous studies have shown that elevated remnant cholesterol (RC) was associated with stroke risk. There is insufficient evidence on the relationship between 2‐year changes in RC and stroke risk in the general population. Our aim was to explore the relationship between 2‐year changes in RC and the risks of stroke and its subtypes in the general population. Methods The study included 62 443 individuals who were free of stroke from the Kailuan Study. Two‐year changes in RC was defined as the difference between the RC in 2008 and that in 2006. Multivariable‐adjusted Cox proportion models were used to examine the associations between 2‐year changes in RC with the risks of stroke and its subtypes. Results During a median follow‐up period of 10.30 years, 3780 (6.38%) stroke events occurred. The changes in RC were positively associated with the risk of stroke, after adjustment for multiple potential confounders. The hazard ratio (HR) for the Q4 group versus the Q1 group was 1.14 (95%, CI, 1.02–1.28) for stroke, and 1.18 (95% CI, 1.04–1.32) for ischemic stroke. The risks of stroke were higher in the RC increased group than the RC nonincreased group. The HR was 1.12 (95% CI, 1.04–1.20) for stroke, and 1.15 (95% CI, 1.07–1.24) for ischemic stroke. Conclusions Substantial changes in RC are associated with increased risks of stroke in the general population. Monitoring long‐term changes in RC may assist with the early identification of individuals at high risk of stroke.